2021
DOI: 10.1038/s41598-021-85984-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing flotation separation of chalcopyrite and magnesium silicate minerals by surface synergism between PAAS and GA

Abstract: Separation effects of sodium polyacrylate (PAAS) and gum Arabic (GA) on flotation of chalcopyrite and magnesium silicate minerals using potassium butyl xanthate (PBX) as collector were investigated by micro-flotation experiments, zeta potential, Infrared spectral (IR), SEM–EDS, XPS analysis and copper sulphide ore beneficiation test. The micro-flotation experiments and zeta potential measurements showed that combined depressant consisting of PAAS and GA could efficiently reduce the recoveries of mixed minerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Through molecular dynamics simulation, PAA was reported to adsorb on quartz and clay mineral surfaces, ultimately preventing agglomeration of the tailings and allowing easy dewatering. Chen et al [25], during the flotation separation of chalcopyrite and magnesium silicates with potassium xanthate (a collector) and gum Arabic (a depressant), found that the presence of a PAA-based polymer (sodium polyacrylate) improved the process. The synergism between sodium polyacrylate and gum Arabia allowed selective depression of magnesium silicate minerals, namely talc and serpentine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through molecular dynamics simulation, PAA was reported to adsorb on quartz and clay mineral surfaces, ultimately preventing agglomeration of the tailings and allowing easy dewatering. Chen et al [25], during the flotation separation of chalcopyrite and magnesium silicates with potassium xanthate (a collector) and gum Arabic (a depressant), found that the presence of a PAA-based polymer (sodium polyacrylate) improved the process. The synergism between sodium polyacrylate and gum Arabia allowed selective depression of magnesium silicate minerals, namely talc and serpentine.…”
Section: Introductionmentioning
confidence: 99%
“…The synergism between sodium polyacrylate and gum Arabia allowed selective depression of magnesium silicate minerals, namely talc and serpentine. The improved flotation separation was attributed to the PAA dispersion effect in removing serpentine particles from the surface of the talc, which allowed gum Arabia to adsorb on the talc surface [25]. In size reduction units, using these GAs, such as PAA, makes it inevitable that these additives can directly or indirectly enter downstream separation processes, such as flotation.…”
Section: Introductionmentioning
confidence: 99%